2012
DOI: 10.1037/a0029210
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-group responders in methamphetamine pharmacotherapy trials: The role of immediate establishment of abstinence.

Abstract: Objective Treatment responses of placebo groups in addiction medicine trials have important implications for research methodology and clinical practice, however, studies examining placebo group responses in addiction medicine is scarce. Extant data suggests the importance of early treatment responsiveness for long-term outcomes. Among methamphetamine (MA) dependent individuals randomized to placebo pill plus behavioral support conditions in pharmacotherapy development trials, we hypothesized that immediate abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…That temporal responders were more likely to be observed among those who presented a stimulant metabolite-free urine sample at intake is consistent with prior analyses of outcomes in trials of methamphetamine treatments that show strong correlations between start-of-intervention drug use status and intervention response (Brensilver et al, 2012; Cochran, Stitzer, Nunes, Hu, & Campbell, 2014). Patterns of intervention response observed in this study also are consistent with findings from early studies of CM used in methadone maintenance clinics (Morral et al, 1997), though the identification of a single positive responder pattern is unique to this study.…”
Section: Discussionsupporting
confidence: 83%
“…That temporal responders were more likely to be observed among those who presented a stimulant metabolite-free urine sample at intake is consistent with prior analyses of outcomes in trials of methamphetamine treatments that show strong correlations between start-of-intervention drug use status and intervention response (Brensilver et al, 2012; Cochran, Stitzer, Nunes, Hu, & Campbell, 2014). Patterns of intervention response observed in this study also are consistent with findings from early studies of CM used in methadone maintenance clinics (Morral et al, 1997), though the identification of a single positive responder pattern is unique to this study.…”
Section: Discussionsupporting
confidence: 83%
“…Prominent among these individual differences are the drug(s) endorsed as the primary problem, and reason for treatment entry, and the current drug use status of the individuals entering treatment. In clinical trials with stimulant abusers, it repeatedly has been shown that a substantial proportion has already achieved abstinence prior to treatment entry or does so rapidly upon treatment entry, and that early drug abstinence is strongly associated with better treatment prognosis [ 1 - 16 ]. Studies among alcohol users receiving treatment similarly have described divergent pre-treatment drinking patterns, including pre-treatment abstinence, and have demonstrated their association with treatment outcomes [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have shown a relationship between early treatment response and positive outcomes in clinical trials of substance use treatments [14][15][16][17][18]. Early abstinence is associated with better retention in out-patient behavioral and pharmacological treatment programs for opiate use [19][20][21].…”
Section: Introductionmentioning
confidence: 99%